Incremental Planning: The Tsawwassen First Nation Experience - Millette, Daniel M. (Journal of Aboriginal Economic Development, 2014)
In terms of community planning in Canada, it can easily be argued that the Tsawwassen First Nation in British Columbia is undergoing one of the most challenging processes in present-day planning practice. Since the signing of the Tsawwassen First Nation Final Agreement — the first contemporary urban treaty in the country, several economic development activities have been negotiated, all within a comprehensive land use planning strategy initiated by Tsawwassen Chief Kim Baird, that can only be referred to as 'innovative' and 'bold'. Several multimillion dollar projects are in the works, including a four hundred (400) million dollar shopping mall, an inland port, and a series of subdivisions that will eventually accommodate 4,000 new residents.The planning process of integrating the First Nation lands within a peri-urban framework, all-the-while maintaining a progressive, jurisdictional approach that places traditional values, transparency and community well-being at the forefront of a list of several important and at times competing planning tenets, is, at best, ambitious. The objective, to Chief Baird, is to create an economy that welcomes investment, all-the-while attracting families, within a First Nation regime that is fair to all stakeholders.The journey has been a long one, having its roots in colonial times, with the Chief's great grand-father's eventual address to the McKenna-McBride Commission, adhering to the British Columbia Treaty Commission's Treaty Process, becoming a signatory to the Framework Agreement on First Nation Lands Management, and culminating in what would arguably be the most significant urban treaty in Canadian history — the Tsawwassen First Nation Final Agreement. The whole has provided for a complex blend of lands whose uses together must satisfy needs that extend from the culturally important past into an economically viable future. The land use planning process for this very special set of lands and stakeholders is therefore not straightforward, having required an incremental approach that is novel and worth consideration for other communities undergoing rapid change.